DEKULTURASI BENTUK SENI PERTUNJUKAN ORKES GAMBUS DI KOTA PARIAMAN PROVINSI SUMATERA BARAT - GANI, IMRAN ABDOEL (Jurnal Seni Musik, 2019)
This study focused on developments that occurred in gambus music in the Pariaman area from 1960 to 2018. Many other interesting changes that occurred in the development of stringed music in this area. Lute music is a musical unit that presents musical instruments gambus, especially playing Arabic songs and qasidah. The development of lute music in Indonesia began in the 19th century along with the arrival of Arab immigrants from Hadramaut, South Yemen to the archipelago. Although initially gambus was a means of preaching immigrants, along with the gambus, it developed into a means of entertainment. In 1970, Nur El-Surayya Gambus Orchestra held a concert in the context of a cultural weekend in Padang Pariaman District, West Sumatra. Nur El-Surayya Gambus Orchestra performances at that time were very welcome for the people of Padang Pariaman. Several years before the arrival of the Nur El-Surayya Gambus Orchestra to Padang Pariaman Regency, in this area several gambus music groups were established which are well known today, namely: Al Falah Gambus Orchestra (1960-1980), Al Ihsan (1965) , Nurul Hidayah (1974), and Al Hidayah (1995-present). The musical instrument used by the Al Falah Gambus Orchestra is currently an acoustic music instrument such as: violin, gambus (Ud), tamburin, bass barge / betot bass, and maracas. This study specifically examines the "Deculturation of the Forms of Performing Gambus Orchestra in the City of Pariaman, Province of West Sumatra, Musicological Study" using qualitative research methods. data collection used in this study are, observation, interviews, documentation and data analysis. This method is designed to reveal the phenomenon of the Gambus Orchestra in Kota Pariaman.